Community perception toward mangrove restoration program in Kampung Nelayan Seberang, Medan - Thoha, Achmad Siddik; Onrizal; Agus Purwoko; Alfan Gunawan Ahmad; Tika Yuana Sari (Talenta Publisher, 2024)
Indonesia has the largest mangrove forests in the world. However, Indonesia is also listed as the largest contributor to loss of the world's mangrove forests. Good mangroves will support the lives of coastal communities and vice versa. Mangrove forests in the area of Kampung Nelayan Seberang, Medan Belawan and its surroundings were also degraded. Therefore, degraded mangrove forests need to be restored through mangrove restoration activities with the involvement of the surrounding community. This community service activity through the Assisted Village Program will carry out mangrove restoration activities with the people of Kampung Nelayan Seberang. The success of restoration activities is determined by good understanding of the mangrove ecosystem and the commitment of the community to be involved in restoring it. The objective of this study was to identify understanding related to mangrove ecosystems and community perceptions of its restoration efforts. Collecting data was carried out by interviewing respondents who represented the population. Descriptive analysis is used to describe the socio-economic conditions, understanding and perceptions of the community regarding ecosystems and mangrove restoration. Generally, respondents understand the role of mangrove forests and agree that mangrove restoration must be done together. Amount of 53 - 83% of respondents agreed and understood that mangrove restoration is important for life and has an impact on income, social and cultural life. The results showed that 60 - 90% of respondents around the restoration area need a rehabilitation program and are willing to be involved in a mangrove restoration program with the parties.